Implementation of Ki Hadjar Dewantara's Education Concept in Implementing Student Character in Class IV Elementary School - Pitriadi, Adi Pauji; Syaodih , Ernawulan; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2022)
Ki Hadjar Dewantara's conception, which is in accordance with the values of Pancasila in the second principle of just and civilized humanity, is contained in several Pancadarma concepts, namely culture and humanity. In the Pancadarma concept of culture, it is interpreted that humans must be ideal human beings who live with full civility. That is, humans must live by always upholding the values of identity that rely on the values of civilized culture. Humans must have noble character or good behavior according to their human nature. In addition, fair and civilized human values are also contained in Ki Hadjar Dewantara's conception which is contained in one of the five pancadarma values, namely humanity. Character is a dynamic organization in the individual psycho-physical system that determines the behavior and thoughts of individuals specifically and leads to human behavior. Character is not just a personality because actually character is a valuable personality. Personality is considered as a characteristic, characteristic, style, characteristic of a person who comes from the formations received in the environment, for example family in childhood, and also innate someone from birth.